SYNTHESIS OF TETRAHYDROHEXAGAMAVUNON-5 AND TETRAHYDROHEXAGAMAVUNON-7 - Ritmaleni Ritmaleni; Ian Praditya; Haryono Wibowo; Sardjiman Sardjiman (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
Synthesis of Tetrahydrohexagamavunon-5 (THHGV-5) and Tetrahydrohexagamavunone-7 (THHGV-7) were prepared by catalytic hydrogenation reaction on Hexagamvunon-5 (HGV-5) and Hexagamavunone-7 (HGV-7) by using gas H2 as source of hydrogen gas, Pd/C 10 % as metal catalyst and methanol as solvent at room temperature. The products were characterized by IR Spectroscopy, Gas Chromatography-Mass Spectroscopy (GCMS), 1D-NMR (1H-NMR and 13C-NMR) and 2D-NMR (1H-13C HMQC) Spectroscopy to determine the product structure molecules. According to the data of IR, GC-MS, 1H-NMR, 13C-NMR and 1H-13C HMQC spectra, the products are THHGV-5 and THHGV-7 as white crystalline powders. Key words:Tetrahydrohexagamavunon-5, Tetrahydrohexagamavunone-7, Hexagamvunon-5, Hexagamavunone-7